ETHNIC MINORITY FEMALE HUMAN RESOURCES WITH CURRENT DEVELOPMENT SOCIO-ECONOMIC IN MOUNTAINOUS AREAS OF VIETNAM - Dao Mai Phuoc; Le Huong Giang (American Journals Publishing, 2022)
Human resources are the greatest asset, a decisive factor for the existence and development of the country. In the mountainous areas of our country, ethnic minority human resources are a central factor, playing an important role in socio-economic growth and development. In the revolutionary cause, our Party and State give special priority to investment and development of human resources in mountainous areas to meet the requirements of each period.
Keywords: Women, ethnic minorities, mountainous areas, Vietnam